Leveraging Cloud Computing and Artificial Intelligence Capability to Strengthen Good Governance in Public Organizations: The Mediating Role of Innovation Strategy - Vivi Oktari (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2026)
This study aims to analyze the influence of Cloud Computing and Artificial Intelligence (AI) Capability on Good Governance in public organizations, as well as to examine the mediating role of Innovation Strategy in these relationships. This quantitative study was conducted among 250 civil servants of the Provincial Goverment of DKI Jakarta, Indonesia. Data were collected using structured questionnaires measuring cloud computing utilization in administrative and technical processes, employees’ AI capabilities, innovation strategy implementation, and good governance practices. The relationships among these variables were analyzed using Structural Equation Modeling (SEM). The results reveal that Cloud Computing has a significant and positive effect on Good Governance, indicating that digital infrastructure enhances transparency, accountability, and administrative efficiency in public service delivery. However, AI Capability does not have a direct impact on governance quality, suggesting that technological sophistication alone is insufficient without strategic and organizational alignment. Furthermore, Innovation Strategy demonstrates a strong positive effect on Good Governance and plays a significant mediating role between both Cloud Computing and AI Capability. This implies that innovation-oriented management serves as a key enabler that transforms technological potential into governance effectiveness. Overall, the findings highlight the critical importance of innovation-driven strategies in realizing the benefits of AI and cloud technologies for public sector transformation. The study contributes to the growing body of research on digital governance by integrating perspectives from the Resource Based View (RBV) and Dynamic Capability Theory, emphasizing that technological adoption must be complemented by strategic innovation and institutional readiness to achieve sustainable governance performance.